Air Pollution Dispersion Modelling using GRAL in Area Near Coal-Steam Power Plant at Central Java - Januar Arif Fatkhurrahman; Ikha Rasti Julia Sari; Yose Andriani (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2021)
Sulfur dioxide and Nitrogen dioxide were significant emissions emitted from coal-steam power plants that may cause health problems for humans and damage the environment. Studying the SO2 and NO2 gradients in Indonesian residential communities is critical for evaluating resident's SO2 and NO2 exposure. The method developed to assist analysis of spatial SO2 and NO2 gradients on a community scale combines a mesoscale Lagrangian dispersion model with field observations around coal-steam power plants using GRAL. The objectives of this study focused on GRAL dispersion of SO2 and NO2 in an Indonesian residential community near the coal-steam power plant, with a 6 km x 8 km resolution. Analysis of this model indicates a correlation between simulation and observation, with SO2 coefficient correlation (R) within 0.5 – 0.82 and NO2 coefficient correlation (R) within 0.30 – 0.59. Model performances analyze by NMSE and FB. The SO2 model is comparable to observation data since it has a better average NMSE and FB than the NO2 model. Due to data limitation of observation collected by grab sampling instead of continuous ambient measurement system affect different respond time compared with hourly data from the model.